2017
DOI: 10.1111/1759-7714.12510
|View full text |Cite
|
Sign up to set email alerts
|

Differential protein‐coding gene and long noncoding RNA expression in smoking‐related lung squamous cell carcinoma

Abstract: BackgroundCigarette smoking is one of the greatest preventable risk factors for developing cancer, and most cases of lung squamous cell carcinoma (lung SCC) are associated with smoking. The pathogenesis mechanism of tumor progress is unclear. This study aimed to identify biomarkers in smoking‐related lung cancer, including protein‐coding gene, long noncoding RNA, and transcription factors.MethodsWe selected and obtained messenger RNA microarray datasets and clinical data from the Gene Expression Omnibus databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 39 publications
0
21
1
Order By: Relevance
“…Study of miRNAs has dominated the field of noncoding RNA regulation in the past decade . Recently, more and more studies have indicated that lncRNAs provide a growth advantage to malignant cells, resulting in progressive and uncontrolled tumor growth . This provides us with new directions for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Study of miRNAs has dominated the field of noncoding RNA regulation in the past decade . Recently, more and more studies have indicated that lncRNAs provide a growth advantage to malignant cells, resulting in progressive and uncontrolled tumor growth . This provides us with new directions for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to normal lung tissue, linc01433 is significantly overexpressed and promotes migration and invasion in NSCLC . LINC00094 is highly expressed in lung cancer tissues and could be a molecular target for therapy for smoking‐related lung cancer . In recent years, emerging evidence has confirmed the role of lncRNAs in drug resistance …”
Section: Long Non‐coding Rnas (Lncrnas) and Non‐small Cell Lung Cancementioning
confidence: 99%
“…15 Moreover, microarray analysis showed that LINC00094 is down-regulated in MEM-incubated cells. 15 Moreover, microarray analysis showed that LINC00094 is down-regulated in MEM-incubated cells.…”
Section: Zhu Et Almentioning
confidence: 99%
“…It has been reported that LINC00094 may as a prognostic biomarker of lung cancer. 15 Moreover, microarray analysis showed that LINC00094 is down-regulated in MEM-incubated cells. However, the regulatory role and potential mechanisms of LINC00094 affecting the BBB permeability have not been investigated.…”
mentioning
confidence: 99%